1989
DOI: 10.1007/bf00580965
|View full text |Cite
|
Sign up to set email alerts
|

Localization of transport compartments in turtle urinary bladder

Abstract: To characterize different transport compartments in the urinary bladder epithelium of postabsorptive turtles, the electrolyte composition of individual cells was determined using electron microprobe analysis. After blocking the transepithelial Na transport, the short-circuit current decreased from positive to negative values (from 26.5 +/- 17.7 to -3.9 +/- 2.9 after ouabain and from 25.4 +/- 17.2 to -8.0 +/- 5.1 microA/cm2 after amiloride). Whereas under control conditions the Na and K concentrations were simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…Whereas the concentrations of Na, K and Cl typically located in the free cyto plasm were much smaller than in basal cell areas, S and Ca concentrations were much higher. Similar element compositions were observed in other mucin granule-containing epithelial cells such as the goblet cells of the colon [14] and the toad urinary bladder [15] and the granular cells of the turtle urinary bladder [16], Whereas in about 85% of upper and lower gland cells the Na concentration was very homogeneous and only 10 mmol/kg ww, it was variable and about 40 mmol/kg ww high er in the remaining cells. Whether the differ ent Na concentrations belong to different cell types, or whether the high Na concentration in some of the cells reflects beginning cell death cannot be answered by the present study.…”
Section: Cellular Electrolytes Under (Jssing Conditionssupporting
confidence: 77%
“…Whereas the concentrations of Na, K and Cl typically located in the free cyto plasm were much smaller than in basal cell areas, S and Ca concentrations were much higher. Similar element compositions were observed in other mucin granule-containing epithelial cells such as the goblet cells of the colon [14] and the toad urinary bladder [15] and the granular cells of the turtle urinary bladder [16], Whereas in about 85% of upper and lower gland cells the Na concentration was very homogeneous and only 10 mmol/kg ww, it was variable and about 40 mmol/kg ww high er in the remaining cells. Whether the differ ent Na concentrations belong to different cell types, or whether the high Na concentration in some of the cells reflects beginning cell death cannot be answered by the present study.…”
Section: Cellular Electrolytes Under (Jssing Conditionssupporting
confidence: 77%
“…This element composi tion, which differs considerably from that in basal cell regions, might be caused by the mucus located within large apical mucin gran ules. Similar element compositions have been observed for other mucin granule-containing epithelial cells [20,23]. Compared with the present data, chemical analysis has yielded higher intracellular Na and Cl and lower K concentrations [24], The reason for this dis crepancy might be that the radioiodinated se rum albumin, used as extracellular space marker in the chemical analysis, does not assess the extracellular space completely, meaning that a fraction of the extracellular space (high Na and Cl and low K concentra tions) is falsely regarded as cellular.…”
Section: Discussionsupporting
confidence: 82%
“…The treatment of the animals prior to the experiments, dissection of the bladders, and incu bation of isolated bladder pieces in Ussing-type cham bers (exposed area 0.75 cm2) were similar to previously described procedures [3]. Because the animals were not fed during the 7 days prior to the experiments they can be regarded as 'postabsorptive'.…”
Section: Methodsmentioning
confidence: 99%
“…The epithelium of the turtle urinary blad der consists of three different cell types, granular, basal, and carbonic-anhydrase-rich (CA) cells [1,2], Whereas granular and basal cells probably form a syncytial transport compart ment [3] involved in Na+ absorption [3][4][5], the CA cells seem to be responsible for acid-base secretion and Cl-absorption [6], Ultrastructural investigations have demonstrated that H+ secretion is performed by a-type, and HCO3 secretion by (3-tvpe CA cells [7]. Sev eral lines of evidence indicate that the mem brane transporters primarily involved in acid and ordinary base secretion are an H+ translo cating ATPase and an anion exchanger [8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation